Morphological Development of the Hip in Normal Infants Under Six Months of Age by the Graf Ultrasound Method - Liu, Bing; Hu, Xiaoyun; Li, Lianyong; Gao, Shuxi (Frontiers in Pediatrics, 2022)
Objective: This large-sample observational study aims to analyze the morphological development of the hip joint in Chinese normal infants under 6 months of age by the Graf ultrasound method. Methods: The clinical and ultrasound data of infants who underwent early screening for developmental dysplasia of the hip (DDH) in the authors’ clinic from January 2011 to December 2019 were analyzed retrospectively. The standard Graf method was used to measure the hip joint α angle, β angle and femoral head coverage (FHC). The infants with Graf typeⅠor IIa hips were included in this study. All infants were grouped by age. FHC, α and β angles were compared among different study groups. Results: A total of 3067 infants (6134 hips) were included in the study. There were 1164 males and 1903 females with an average age of 77 days (1-180 days). The mean α angle was 62.4° ± 3.6° on the left and 63.2° ± 3.5° on the right (P<0.001). The mean β angle was 55.6° ± 4.5° on the left and 54.8° ± 4.5° on the right (P<0.001). The average FHC was 54.2% ± 4.6% and 54.8% ± 4.2%, accordingly (P<0.001). The α angle and FHC of females was significantly smaller than that of males (P<0.001). While the left β angle in females was slightly larger than males (P=0.014), there were no significant differences in the right β angle between the two sexes (P=0.150). During the first 3 postnatal months, the α angle and FHC increased while β angle decreased with age. However, the α and β angles and FHC were stable at a relatively constant level from the 4th to the 6th postnatal month. Conclusions: The normal infant hip reveals progressive maturation during the first 3 months after birth, and then enters a plateau period during the 4th to 6th month. The development of hip joint in females and of the left side slightly lags behind that in males and of the right side, which is consistent with the observation that DDH is more common in females and on the left hips.